Spring 1999 report, John Van Dyk - Van Dyk, John, 1936-et al (1999)
An annotated list of birds sighted by John Van Dyk dated June 1, 1999. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of spring 1999. Epson - sheet feed